The impact of undernutrition on the association between hypomagnesemia and dynapenia in older women - Ozcan Uzun; Cihan Heybeli; Lee Smith; Nicola Veronese; Masoud Rahmati; Andre Hajek; Pinar Soysal (BMC Geriatrics)
Abstract Objectives To determine the association between hypomagnesemia and dynapenia in older women with different nutritional status. Methods This cross-sectional study included older women who attended one outpatient geriatric clinic. Undernutrition was defined according to the Mini Nutritional Assessment score (MNA) (< 23,5), and handgrip strength of < 16 kg on dynamometer was defined as dynapenia. The association between hypomagnesemia (serum magnesium < 1.7 mg/dL) and dynapenia was determined by logistic regression analysis. Results Among the 933 older women (mean age 81 ± 8), the prevalences of undernutrition and hypomagnesemia were 61% and 15%, respectively. The risk of hypomagnesemia increased with each step of decline in nutritional status, and undernutrition was associated with hypomagnesemia (OR 1.64, 95% CI 1.11–2.43, p = 0.013) In the entire cohort, hypomagnesemia was associated with dynapenia (OR 2.01, 95% CI 1.35-3.00, p = 0.001). In well-nourished patients, hypomagnesemia was not associated with dynapenia, even when unadjusted. However, in the undernourished group, hypomagnesemia was associated with dynapenia after adjusting for age, diabetes mellitus, hypertension, coronary heart disease, Barthel and Lawton scores, polypharmacy, glomerular filtration rate, serum albumin, hemoglobin, and MNA score (OR 2.95, 95% CI 1.04–8.32, p = 0.040). The coexistence of hypomagnesemia and undernutrition (versus neither of them) was significantly associated with dynapenia (OR 4.44, 95% CI 2.67–7.41, p < 0.001). Conclusion The prevalence of hypomagnesemia increases with worsening nutritional status. Hypomagnesemia is associated with dynapenia in older women who are undernourished, even after adjusting for nutritional status, but not in those who are well nourished. The coexistence of undernutrition and hypomagnesemia increase the risk of dynapenia substantially.